Challenging the maximum rooting depth paradigm in grasslands and savannas. (12th January 2015) - Nippert, Jesse B.; Holdo, Ricardo M.
Summary: For many grassland and savanna ecosystems, water limitation is a key regulator of individual plant, community and ecosystem processes. Maximum rooting depth is commonly used to characterize the susceptibility of plant species to drought. This rests on the assumption that deep‐rooted plant species would have a greater total volume of soil water to exploit and should be less susceptible to episodic changes in water availability. Independent of maximum rooting depth, rooting strategies based on differences in biomass allocation with depth, uptake plasticity in relation to water availability and variation in water transport capability may all influence growth responses and susceptibility to drought. Many examples from grasslands and savannas reflect these rooting strategies among coexisting grass, forb and woody species. Here, we use a dynamic model of plant water uptake and growth to show how changes in root distribution, functional plasticity and root hydraulic conductivity have the potential to influence aboveground biomass and competitive outcomes, even when maximum rooting depth remains constant. We also show theoretically that shifts in root distribution to surface soils without changes in maximum depth can potentially outweigh the benefits of increased maximum rooting depth. Combining our current reliance on biogeographic descriptions of maximum rooting depth with insights about other, more subtle aspects of root structure and function are likely to improve our understanding of ecosystem responses to dynamic water limitation. Abstract : Lay Summary